Evidential adjectives in Lithuanian academic discourse - Ruskan, Anna (Kalbotyra, 2012)
The present study explores the functional distribution of the neuter adjectives akivaizdu ‘evident, obvious’, aišku ‘clear’, natūralu ‘natural’ and panašu ‘likely’ in Lithuanian written academic discourse. The research focuses on the CTP (complement-takingpredicate) and parenthetical use of the adjectives and presents basic quantitative and qualitative findings of these patterns of use. The data have been collected from the Corpus of Academic Lithuanian represented by texts from biomedical sciences, humanities, physical sciences, social sciences and technological sciences. The research shows that the adjectives under consideration primarily express the source of information the author uses for a claim but not the author’s degrees of commitment towards the proposition. These adjectives signal that the author obtains knowledge for the proposition through inferences based on external and/or internal sources of evidence. Inferences in academic discourse are intersubjective as they mark the availability of evidence to the reader.